The sense of security in the face of the war in Ukraine. Comparative study of Poland and the Czech Republic - Tomasz Marcinkowski; Juliusz Sikorski; Lukas Vomlela (Eastern Journal of European Studies)
The article examines the impact of the war in Ukraine on the sense of security among university students in Poland and the Czech Republic, comparing their perceptions and susceptibility to disinformation. The study reveals that while the majority of students in both countries feel safe, a significant portion experienced increased fear immediately after the war began. The research highlights the differences in attitudes toward the European Union's and national governments' actions, with Czech students generally more positive. Additionally, the study finds a concerning level of belief in conspiracy theories related to the war, especially among Polish students. The article emphasizes the need for further research to understand the interplay between disinformation, security perceptions, and political attitudes in these countries.